Artefak Rijang Situs Gua Pawon - Nurfaridah, Dinar; Bawono, Rochtri Agung; Kristiawan, Kristiawan (Humanis; Vol 23 No 4 (2019)DO - 10.24843/JH.2019.v23.i04.p05, 2019)
Goa Pawon is a prehistoric site that very important to discover the growth of ancient society in the world. Not only found humans remains in Goa Pawon, but we also found so many artefacts and ecofact remains, one of the artefacts is a tool from chert. This research is intended to discover the variety type of chert tools and to uncover what is the function of every type of chert tools that used to sustain human life in Goa Pawon. Data collecting method used for this research is bibliography study, observation, and interview. All the finding then collected and analyzed. Research method used for this research is typology analysis method, and function analysis method. Typology theory, functional theory and behavior archaeology theory is use by the researcher to be the basic idea about the type and function of rijang that used by the humans of Goa Pawon. The findings of chert artefacts in Goa Pawon is split into two category, waste category and tools category. Waste category has flakes, debitage, and core. Tool category has edge scrapper, notched scrapper, end scrapper, danticulated scrapper, high-back scrapper, lancipan dan multi tools. All the tools in this site have so many form and made typical adjusted to what is for. Tendency for rijang is used to process animals, for example is pointer that was function to make a hole on animal bone and animal tooth and made to be a jewelry, and notched scrapper that used to dredge a molusca, Pelecypoda type.